Value-Sharing and Uniqueness of Entire Functions - Wu, Chun (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the uniqueness of entire functions sharing a nonzero value and obtain some results improving the results obtained by Fang, J. F. Chen, X.Y. Zhang and W. C. Lin, et al.